Epistemic and non‐Epistemic Theories of Remembering. (4th April 2016) - James, Steven
Abstract: Contemporary memory sciences describe processes that are dynamic and constructive. This has led some philosophers to weaken the relationship between memory and epistemology; though remembering can give rise to epistemic success, it is not itself an epistemic success state. I argue that non‐epistemic (causal) theories will not do; they provide neither necessary nor sufficient conditions for remembering that p . I also argue that the shortcomings of the causal theory are epistemic in nature. Consequently, a theory of remembering must account for both its fundamentally epistemic nature and for its constructive and dynamic processes.